2018
DOI: 10.1590/1678-7757-2017-0154
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different restorative materials on periodontopathogens in combined restorative-periodontal treatment

Abstract: Objective The aim of the study was to evaluate the association between subgingival restorations and the target periodontopathogenic bacteria (Pg, Td and Pi) in subgingival biofilm during one year after combined restorative-periodontal treatment.Material and Methods Seventeen systemically healthy subjects, who were positive for the presence of three cervical lesions associated with gingival recessions in three different adjacent teeth, were included in the study. A total of 51 combined defects were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Moreover, in a recent clinical study, the influence of different subgingival restorations on periodontal health was evaluated via combined restorative‐periodontal treatment. The results indicated that irrespective of the type of restorative materials, the subgingival restorations did not produce significant changes in clinical and microbiological examinations 12 months after surgery [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent clinical study, the influence of different subgingival restorations on periodontal health was evaluated via combined restorative‐periodontal treatment. The results indicated that irrespective of the type of restorative materials, the subgingival restorations did not produce significant changes in clinical and microbiological examinations 12 months after surgery [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed varying degree of bacterial colonization when they compared different restorative material to each other or teeth. Furthermore, studies stated that the biological outcome was analyzed by assessing probing depth and plaque level [5].…”
Section: Introductionmentioning
confidence: 99%